RUPTURED HEPATIC ARTERY ANEURYSM SUCCESSFULLY TREATED WITH DUAL-LAYER STENT ENDOVASCULAR TREATMENT: CASE REPORT AND LITERATURE REVIEW - Curakova Ristovska, Elena; Darko DJambaz; Janevski, Petar; Genadieva Dimitrova, Magdalena; Todorovska, Beti; Nikolovska Trpchevska, Emilija; Janevski, Georgi; Antovikj, Svetozar; Rankovic, Ivan; Ivanoska Jankovska, Violeta; Hadzi Nikolova Alcinova, Natasha; Grivcheva Stardelova, Kalina; et al. (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2024)
Spontaneous rupture of a hepatic artery aneurysm into the peritoneal cavity is a serious life-threatening complication related to hemodynamic instability and high mortality rate. We present a case of a hepatic artery aneurysm complicated with intraperitoneal bleeding and successfully treated with endovascular stent insertion. A 78-year-old male patient was admitted to a tertiary care center due to an abdominal pain and a large amount of free fluid in the peritoneal cavity. The diagnostic paracentesis confirmed hemoperitoneum. The CT scan revealed an aneurysm of the common hepatic artery that was successfully treated with an insertion of a dual-layered carotid stent. Endovascular stent insertion of a ruptured aneurysm of the common hepatic artery is an effective therapeutic procedure that can provide a definitive curative treatment in some patients.
Keywords: hepatic artery aneurysm; hemoperitoneum; endovascular stent